PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PERUSAHAAN FOOD & BEVERAGE - Saraswati, Carla; Njotoprajitno, Rosemarie Sutjiati (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2022)
Financial distress is a kind of condition where a company has experiencing difficulties in financial in fulfilling its various obligations (insolvency). Several food & beverage sub sector companies have shown a significant decline in profits in their first quarter performance in 2019. This shows there is a threat of financial distress. This study tries to determine/examine the effect of financial ratios on financial distress in manufacturing companies engaged in the food and beverage in Indonesia Stock Exchange (IDX) for 2015 to 2019. 18 (eighteen) companies are examined. The statistical method used in this study is regression logistics. It can be concluded that the ratio of profitability, liquidity ratio, and ratios activity have no effect on financial distress. While, the market ratio, solvency ratio has an effect on financial distress.